An empirical analysis of process improvement from best practice adoption: A study of stroke care best practices - Lee, Brandon; Fredendall, Lawrence D.; Roth, Aleda V.; Sternberg, Shannon; Quiroga, Bernardo F. (Journal of Operations Management, 2024)
This study empirically examines how induced learning through adopting a set of best practices and learning‐by‐doing improved a hospital's care of ischemic stroke patients using ad hoc teams. While previous studies in healthcare operations management conducted in ad hoc team environments predominantly focused on volume‐based learning (learning by doing, team familiarity via interactions among team members), our study focuses on induced learning in ad hoc teams through best practice adoptions. The analysis uses secondary data (Data period: January 2009–March 2017) about stroke patients from a comprehensive stroke center (CSC) in a U.S. tertiary teaching hospital as it adopted the U.S. American Heart Association/American Stroke Association (AHA/ASA) Target:Stroke best practices. The ad hoc stroke teams provide the initial care and their performance is measured using “ Door‐to‐Needle (DTN) ” time and its sub‐time segments. The DTN time is measured as the time elapsed between the stroke patient's arrival at the hospital's emergency department (ED) and the appropriate infusion of “ Tissue Plasminogen Activator (TPA) ” (i.e., a thrombolytic medication informally referred to as a “clot buster”). We found that adopting these best practices improved ischemic stroke care beyond improvement due to repetition. We also found that the neurologist's recent experience providing stroke care for the prior patient is positively associated with meeting the time performance goal for the current patient. This study provides insights into the use of management mechanisms to adopt and sustain best practices in healthcare that are generalizable to other organizations with ad hoc team environments.